Deep cooling scheme of quantum degenerate gas and ground experimental verification for chinese space station - Li, Hui; Yu, Jiachen; Yuan, Xiaolong; Wu, Biao; Xie, Yu; Li, Lin; Liang, Angang; Huang, Mingshan; Jin, Shengjie; Xiong, Wei; Wang, Bin; Chen, Dijun; et al. (Frontiers in Physics, 2022)
The Cold Atom Physics Rack (CAPR) of Chinese space station will be launched at the end of 2022. The important goal of CAPR is to achieve BEC at 100 pk. In order to obtain ultracold atoms in microgravity of space station, we propose a two-stage cooling scheme using all-optical trap with different waist beams. The cold atom cloud obtained by this scheme is composed of condensate and thermal atoms around condensate. The design of our two-stage cooling scheme will effectively reduce the temperature of the thermal atom cloud and the effective temperature generated by the interaction energy of the condensate. The atomic temperature of 5 nk is obtained from the ground test experiment, and the corresponding temperature under the microgravity condition of the space station is theoretically predicted to be less than 100pk. Taking the advantages of ultracold temperature and long-time detection, many scientific experiments will be arranged. In this paper, the ground test experiments based on ground principle prototype and pre-prototype for CAPR are also introduced.